Martin Luther King Jr’s Theory of Nonviolence in Conflict Resolution - Eyo Emmanuel Bassey; Ejesi Edwin (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This article on Martin Luther King Jr examines the power of non-violence philosophy in conflict resolution. Before Luther King Jr philosophy of non-violence, Jesus Christ, Mahatma Gandhi, Leo Tolstoy and other advocates of peace had vigorously pursued non-violence as the only tenable and acceptable paradigm in conflict resolution. In this essay, Martin Luther King Jr. is shown to be deeply influenced by his moral and spiritual background upon which his father had endowed upon him. For Luther King Jr, the racial discrimination experienced in Montgomery can only be defeated by non-violence and nothing more, for violence begets violence upon which continuous use of violence leads to the vicious circle of violence. The essay concludes that human beings ought to use non-violence in conflict resolution especially in the face of dehumanization and racial discrimination